Pergeseran Praktik Jual Beli Ke Sistem Arisan Pada Masyarakat Desa Dulamayo Selatan Kabupaten Gorontalo Perspektif Hukum Ekonomi Syariah - Rizal Darwis; Hajira Bilondatu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
Selling and buying goods with the regular social gathering system is the same as selling and buying in general. However, buying and selling with this social gathering system is a sale and purchase that is carried out when one party gets a lottery at the social gathering, only getting goods, not money. This study aims to determine the factors that cause buying and selling of goods with the regular social gathering system and how the perspective of sharia economic law on selling and buying goods with the regular social gathering system in Dulamayo Selatan Village. This research is field research with an empirical juridical approach. Data were collected through observation, interviews, and documentation. Then the data collected were analyzed by qualitative descriptive. Based on the results of the research and discussion carried out, it is known: first, buying and selling goods with the regular social gathering system is carried out because it is caused by internal factors, namely the chairman of the regular social gathering gains from money, the price of goods, and discounts if someone gets a lottery by taking money, as well as other factors external, namely because there are parties who cannot afford to buy goods in the case and because Dulamayo Selatan Village is very far from urban areas. Second, buying and selling goods with the regular social gathering system in Dulamayo Selatan Village; in the view of sharia economic law is not allowed because it contains elements of usury, and the practice of the regular social gathering goods being replaced with money is also not allowed because it violates the agreement at the beginning of the sale and purchase of goods with the regular social gathering system and is detrimental to the regular social gathering members.